Estudio experimental y comparativo de la resistencia a la compresión de muestras de concreto hidráulico sometido a diversas técnicas de curado (2023)
One of the challenges of construction is to guarantee the quality of the properties of the construction materials used, with emphasis on concrete through the curing process, since this is the one that provides significant resistance to the material, so in this project, an experimental study of the compressive strength performance of hydraulic concrete was carried out, using four different curing techniques frequently used in the construction sector (polyethylene plastic sheets, manual curing, standard curing and no curing). These techniques were used in order to highlight the importance of concrete hydration processes and to determine which of the applied curing techniques is the most effective when implemented in civil works. For it, a total of 180 cylindrical specimens of a specific design strength of 21 MPa, were manufactured, cured and tested at 7, 28 and 56 days (15 specimens cured under each of the techniques). According to the results obtained, a higher compressive strength was evidenced in the samples that were cured with polyethylene plastic sheets and the need for the curing process in concrete in the construction of civil works was confirmed.